Digitalization, Circular Economy, and BUMDes Sustainability: Evidence from the Bangka Belitung Islands Province - Rulyanti Susi Wardhani; Suhdi Suhdi; Darus Altin; Alim Bahri; Muhammad Qomaruddin; Mohd Taufik Bin Mohd Suffian (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2026)
This study investigates the relationship between knowledge, attitude, perceived benefits, and support for the sustainability of digitalization in Village-Owned Enterprises (BUMDes) as a community empowerment mechanism within a circular economy framework in Bangka Belitung Islands Province, Indonesia. Motivated by environmental challenges—particularly waste management—and the need to enhance community empowerment through digital transformation, the study employed a convergent mixed-methods design. Quantitative data from 197 BUMDes managers were analyzed using multiple linear regression, while qualitative data from semi-structured interviews with 10 key informants were analyzed thematically. Knowledge and perceived benefits were positively and significantly associated with sustainability support, whereas attitude showed no significant association, reflecting an attitude–behavior gap linked to infrastructural, financial, and institutional barriers identified through qualitative analysis. Managerial knowledge and perceived advantages of digital technologies emerged as primary drivers of digital transformation, while inadequate infrastructure, limited digital competencies, financial constraints, and weak institutional support remained key barriers. These findings suggest that sustaining BUMDes digitalization as a community empowerment tool requires capacity building, institutional strengthening, collaborative governance, and supportive public policies. This study contributes empirical evidence on rural digital transformation, the circular economy, and community empowerment in an archipelagic region, offering practical implications for policymakers and community development practitioners.